Taking the Next Step in the Legal Response to Domestic Violence: the Need to Reexamine Specialized Domestic Violence Courts from a Victim Perspective - Wellman, Kathryn Gillespie (Columbia Journal of Gender and Law, 2013)
S.S. and R.T.’s story involved many of the elements common to domestic violence cases: multiple instances of physical, verbal, and psychological abuse of S.S. by her ex- boyfriend R.T.; initial reluctance on S.S.’s part to report the incident to the authorities out of hope that the violence would simply cease; and the eventual arrest of and entry of an order of protection against R.T. that he repeatedly violated, resulting in the filing of additional charges against him. As these charges moved into court, S.S. assisted the prosecution by providing “detailed written depositions outlining the history and circumstances of the altercations” between her and R.T. Soon afterwards, the case, People v. Tancredi-like many others involving multiple, interconnected matters related to domestic violence in New York-ended up in one of the state’s Integrated Domestic Violence (“IDV”) courts.